Attribute‐Key Attack Against a Class of Key Generation Algorithm Frameworks - Sun, Keshuo; Gao, Haiying; Hu, Bin; Zhou, Aoyang; Zhao, Xiufeng (Concurrency and computation, 2025)
ABSTRACT Attribute‐based encryption (ABE) schemes are widely used for access control of ciphertext in cloud computing. Research on the ability of existing ABE schemes to resist multiple attacks, such as attribute‐key attacks, master‐key attacks, decryption attacks, and so forth, can prevent insecure schemes from being used. This paper summarizes the framework of a class of key generation algorithms in ABE schemes, called Key generation algorithm Under Encoding (KUE) model, based on which we propose the prerequisites for the success of attribute‐key attack. We implement the attribute‐key attack for two typical ciphertext‐policy attribute encryption schemes that fit the KUE model, and reveal the security flaws of the schemes through specific attack examples, which further confirm the practical feasibility of the attack under the KUE model. At last, two countermeasures are proposed against such attacks, providing valuable insights for the design of secure ABE schemes.